EU-US climate cooperation: Challenges and opportunities for the implementation of the Paris agreement - Nataliya Stranadko (Europa-Kolleg Hamburg, Institute for European Integration, 2021)
The transformation from Kyoto to Paris has been analysed by international relations scholars, international law, and transnational governance theory. The international relations literature looks at the climate regime from a perspective of power distribution, state interests, institutions, and multilateral negotiations. International law theory focuses on legal analysis and design of international climate agreements. The transnational governance literature examines the participation of transnational actors at different levels of governance. However, each of these theories overlooks a bilateral trend of cooperation in a multilateral setting that arises as a part of construction or reconstruction of the international regime. Cooperation on climate change between the European Union and the United States deserves special scientific attention. Over the last 30 years of climate negotiations, these nations have met many challenges. However, these challenges currently give opportunities to revise the New Transatlantic Agenda and build a fruitful bilateral partnership and policy coordination in the area of climate change.
Keywords: 320; Bilateral cooperation; climate change; environmental treaties; European Union; global governance; soft law; subnational actors; United States of America